A note on double Laplace transform and telegraphic equations - Eltayeb, Hassan; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
Double Laplace transform is applied to solve general linear telegraph and partial integrodifferential equations. The scheme is tested through some examples, and the results demonstrate reliability and efficiency of the proposed method.